Molecular Mechanism of VSV-Vectored ASFV Vaccine Activating Immune Response in DCs - Yunyun Ma; Junjun Shao; Wei Liu; Shandian Gao; Guangqing Zhou; Xuefeng Qi; Huiyun Chang (Veterinary Sciences)
The vesicular stomatitis virus (VSV)-vectored African swine fever virus (ASFV) vaccine can induce efficient immune response, but the potential mechanism remains unsolved. In order to investigate the efficacy of recombinant viruses (VSV-p35, VSV-p72)-mediated dendritic cells (DCs) maturation and the mechanism of inducing T-cell immune response, the functional effects of recombinant viruses on DC activation and target antigens presentation were explored in this study. The results showed that surface-marked molecules (CD80, CD86, CD40, and MHC-II) and secreted cytokines (IL-4, TNF-α, IFN-γ) were highly expressed in the recombinant virus-infected DCs. In addition, the co-culture results of recombinant virus-treated DCs with naive T cells showed that the Th1- and Th17-type responses were effectively activated. Taken together, the study indicated that the VSV-vectored ASFV vaccine activated the maturation of DCs and the Th1- and Th17-type immune response, which provided a theoretical basis for the development of novel ASF vaccines.